TANGGUNG JAWAB PENGANGKUT AKIBAT KELALAIAN PENGANGKUTAN BARANG: Studi Kasus PT. Tiki Jalur Nugraha Ekakurir Kota Surabaya - Rizky, Chamelia Octamevia (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Increasingly advanced technology in the field of transportation does not rule out the possibility that the carrier will not be negligent in the goods that will be handed over to consumers, such as lost goods, damaged goods and so on. To deal with consumer losses, Indonesia itself has a law that regulates consumers, namely Law no. 8 of 1999 concerning Consumer Protection or commonly abbreviated as UUPK. In this regard, it is important to know to what extent this UUPK has been implemented in consumer protection in the field of goods transportation services, especially PT Tiki Lane Nugraha Ekakurir (JNE). This research uses a juridical-empirical method, which is legal research regarding the application or implementation of normative legal provisions directly to each specific legal event that occurs in society. This research discusses the legal position of PT Tiki Lane Nugraha Ekakurir (JNE) as an entrepreneur or provider of goods delivery services, the rights and obligations between PT Tiki Lane Nugraha Ekakurir (JNE) and consumers, as well as the form of responsibility of the delivery company to consumers regarding goods. which did not survive or were damaged in transit